1998
DOI: 10.1002/(sici)1521-3765(19980615)4:6<1000::aid-chem1000>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Stepwise Assembly and Molecular Growth: [H14Mo37O112]14− and [H3Mo57V6(NO)6O189(H2O)12(MoO)6]21−

Abstract: The understanding of the formation of complex molecular systems from simple building blocks by conservative self-assembly processes is still a challenge. We report the synthesis and structural characterization of the large reduced polyoxometallate compounds (NH 4 oxometallate fragment by air oxidation; this implies that its uptake and release are controlled by the degree of reduction of the cluster. Correspondingly, intermediates between the anions of 2 and 3 of the {Mo 57x V 6 } type could be isolated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 17 publications
(40 reference statements)
1
53
0
2
Order By: Relevance
“…[13] In this paper, we report the oxidation reactions of 1, with or without guest anions, and utilize the cyclic octavanadate framework as a scaffold toward synthesis of a spherical compound. Syntheses of new polyoxovanadates were attempted with the highest oxidation state vanadium atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[13] In this paper, we report the oxidation reactions of 1, with or without guest anions, and utilize the cyclic octavanadate framework as a scaffold toward synthesis of a spherical compound. Syntheses of new polyoxovanadates were attempted with the highest oxidation state vanadium atoms.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, the Mo 57 V 6 cluster has nucleophilic pores that potentially may attract small cations. The M 6 O 6 type pores are interestingly nearly identical to those of the highly celebrated [47,48]. It was shown that all the species Mo 57+x V 6 with x from 0 up to 6 can be formed.…”
Section: Nucleophilicity Of the Oxo Sites -A Unique Reactivitymentioning
confidence: 91%
“…Based on precise EMF measurements and analysis of 17 O and 95 Mo NMR spectra, the speciation in alkali-metal molybdate solutions is dependent upon the ionic medium. [17][18][19][20] Distribution diagrams for 0.6 M Na(Cl) and 3.0 M Na(ClO 4 ) are shown in Figure 3.…”
Section: Aqueous-solution Speciesmentioning
confidence: 99%
“…The aqueous system H þ À HVO 4 2À ÀMoO 4 2À has been investigated by EMF methods and NMR spectroscopy ( 51 V, 95 Mo, 17 …”
Section: Molybdovanadatesmentioning
confidence: 99%
See 1 more Smart Citation